2020
DOI: 10.3390/s20030685
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Traffic State Prediction via Hyperparameter Optimization Based Classifiers

Abstract: Short-term traffic state prediction has become an integral component of an advanced traveler information system (ATIS) in intelligent transportation systems (ITS). Accurate modeling and short-term traffic prediction are quite challenging due to its intricate characteristics, stochastic, and dynamic traffic processes. Existing works in this area follow different modeling approaches that are focused to fit speed, density, or the volume data. However, the accuracy of such modeling approaches has been frequently q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Most of the existing traffic control schemes deploy fixed time program are based on historical traffic information without considering real-time traffic information [49]. Accurate short-term traffic sate prediction have been reported to have numerous applications for intelligent traffic control [50,51]. Numerous research studies have focused on minimizing delay through signalized intersections by rationally optimizing the cycle length.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Most of the existing traffic control schemes deploy fixed time program are based on historical traffic information without considering real-time traffic information [49]. Accurate short-term traffic sate prediction have been reported to have numerous applications for intelligent traffic control [50,51]. Numerous research studies have focused on minimizing delay through signalized intersections by rationally optimizing the cycle length.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The optimization of parameters using the multiobjective optimization problem (MOP) swarm algorithm 53 designed to increase the efficiency of the DBN model. In Zahid et al, 54 optimization of hyperparameters in the various machine‐learning models was proposed to overcome the problem of overfitting 9 . The performance of LSTM in arterial road traffic prediction explained in Mackenzie et al 55 A multitask learning DNN 56 used stacked autoencoder for traffic flow prediction.…”
Section: Related Workmentioning
confidence: 99%
“…It is established that strict enforcement could discourage the drivers from committing traffic violations, and significantly reduce the number of crashes, as well as their severity [ 16 ]. Similarly, studies have shown that pro-active traffic control and forecasting could be very beneficial to monitor dynamic drivers maneuvers, thus ensuring strict compliance traffic regulations and mitigate congestion in urban areas [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%